2014
DOI: 10.5466/ijoms.12.129
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial Development in Rats Fed on Powdered Diet Following Extraction of All Upper Molars

Abstract: Growth of the craniofacial bone is a complex biological phenomenon induced by highly coordinated interaction between genetic and environmental factors. The purpose of this study was to confirm whether the environmental factors, namely powdered diet and extraction of all upper molars, have an influence on the cranium and mandibular bone size, bone volume, mineral bone density, widths between left and right condyles and gonions, and intra-arch widths at the first and third molars in rat mandibles.Ten 5-week-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Since the condylar process height and condylar base width grew similarly between control and experimental young rats, the difference in the cross-sectional surface between the groups may be explained by a change of the condylar shape, in that it must become thinner in order to see this difference in the surface. This change of the condylar shape is in accordance with the results of previous studies, 22,31,32 that reported a smaller condylar size, bone volume, condylar thickness width, and condylar process neck width in the extraction and soft diet groups compared to the control. It could be speculated that if the young experimental rats would be left to grow until the adult age, they would have a smaller condylar average surface than the adult control animals.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Since the condylar process height and condylar base width grew similarly between control and experimental young rats, the difference in the cross-sectional surface between the groups may be explained by a change of the condylar shape, in that it must become thinner in order to see this difference in the surface. This change of the condylar shape is in accordance with the results of previous studies, 22,31,32 that reported a smaller condylar size, bone volume, condylar thickness width, and condylar process neck width in the extraction and soft diet groups compared to the control. It could be speculated that if the young experimental rats would be left to grow until the adult age, they would have a smaller condylar average surface than the adult control animals.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies report similar ages when evaluating young and adult rats. [10][11][12][13][14][15][16][17][18]21,22,[27][28][29]31,32 Due to the active growing phase, young rats showed statistically significantly lower values and a bigger increase of all condylar measurements, when compared to the adult rats. This is consistent with a previous report 17 that compared different masticatory functions on young, growing and mature rats, and with a study 30 that reported an increase of the length and width of rat condylar head from 2 to 7 months of age.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There have been many animal experiments reporting that tooth extraction and soft foods detrimentally affect the development of the facial cranium, mandibular bone, and masticatory muscles [1]- [6]. We have previously reported that raising rats with extraction of the maxillary molars and powdered feed reduces mandibular volume, bone density, mandibular height, and mandibular condyle thickness [7] [8]. However, the mandibular condyle shows particularly active growth during the postnatal growth of the mandible.…”
Section: Introductionmentioning
confidence: 99%
“…These experiments showed a reduction in maxillary width, mandibular height and mandibular condyle thickness, and expansion of the size of the mandibular angle [2] [3] [4] [5] [6]. Similarly, our previous research showed masticatory hypofunction in rats, due to extraction of maxillary molars and a diet of powdered feed, was associated with reduced mandibular volume, bone density, mandibular height, and mandibular condyle thickness [7] [8]. Additionally, we indicated that reduced masticatory function led to deformation and cellular disorders in the condylar cartilage, and diminished ossification and heightened bone resorption in the secondary cancellous bone of the condylar head, resulting in slower ossification, less bone volume, and reduced trabecular thickness [9].…”
Section: Introductionmentioning
confidence: 81%